Text me : ancient Jewish wisdom meets contemporary technology : Jewish resources for understanding, embracing and challenging our evolving digital identities /: ancient Jewish wisdom meets contemporary technology : Jewish resources for understanding, embracing and challenging our evolving digital identities. ([2019]) - Schein, Jeffrey; Amkraut, Brian
No abstract available